(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper presents a novel speed vector control scheme of an induction motor (IM) based on robust adaptive variable structure control (VSC) law and its experimental validation are presented. The design of the speed controller greatly affects the performance and efficiency of an electric drive. The combination of non-adaptive variable structure control (VSC) law with the proportional integral (PI) speed controllers is used to control an induction machine. In this proposal in order to increase the efficiency and to provide high performance, PI controllers are replaced by the adaptive controllers. The mathematical model for the adaptive VSC based on genetic algorithm is presented. Root locus and pole assignment techniques are also proposed along with the transient response technique. The simulation and result of this experiment gives high performance dynamic characteristics, change of motor speed and external load disturbances. To provide a numerical comparison between the controllers, a performance based index speed error is assigned.